1991
DOI: 10.1111/j.1528-1157.1991.tb05624.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Felbamate on Plasma Levels of Carbamazepine and Its Metabolites

Abstract: Felbamate (FBM) is a novel antiepileptic drug (AED) currently undergoing clinical evaluation in the United States. During a controlled clinical trial conducted at the National Institutes of Health Clinical Center, FBM was added to constant carbamazepine (CBZ) monotherapy. CBZ total concentrations were reduced during active FBM treatment (mean reduction 25%, range 10-42%, p less than 0.001). The effect was evident after the first week of treatment and reached a plateau in 2-4 weeks. To clarify the interaction m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
24
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(25 citation statements)
references
References 3 publications
1
24
0
Order By: Relevance
“…3, A, B, and E) and rCYP3A4 (Fig. 3, C (Wilensky et al, 1985;Graves et al, 1989;Theodore et al, 1989;Albani et al, 1991;Theodore et al, 1991;Wagner et al, 1993). Heteroactivation is most evident at low substrate concentrations, resulting in a doubling in activity when combining the highest felbamate concentration (1 mM) and the lowest carbamazepine concentration (10 M).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…3, A, B, and E) and rCYP3A4 (Fig. 3, C (Wilensky et al, 1985;Graves et al, 1989;Theodore et al, 1989;Albani et al, 1991;Theodore et al, 1991;Wagner et al, 1993). Heteroactivation is most evident at low substrate concentrations, resulting in a doubling in activity when combining the highest felbamate concentration (1 mM) and the lowest carbamazepine concentration (10 M).…”
Section: Resultsmentioning
confidence: 99%
“…Instead it was assumed that the low clearance of carbamazepine-ep (Benet et al, 1996b) allows the approximation that CLtot CBZ-ep is independent of hepatic blood flow and proportional to in vitro CLf CBZ-diol ϫ fu plasma . Since fu plasma is not changed by felbamate (Albani et al, 1991), the in vivo ratio of CLtot CBZ-ep control /CLtot CBZ-ep FBM was quantitatively estimated from the ratio of the amount of carbamazepine-diol formed in human liver slices in the absence or presence of felbamate.…”
Section: Cyp3a4 Heteroactivation Associated With Drug Interaction 1253mentioning
confidence: 99%
See 2 more Smart Citations
“…In humans, a weak increase (10%) in apparent oral clearance of the CYP2C9 substrate flurbiprofen was observed after 7 days of treatment with dapsone, a heteroactivator of flurbiprofen in vitro (Hutzler et al, 2001). Finally, a clinically observed drug-drug interaction between felbamate and carbamazepine, causing a decrease in steadystate concentrations of carbamazepine (Albani et al, 1991), has been shown to be quantitatively predicted from in vitro human liver microsomal data (Egnell et al, 2003b).…”
mentioning
confidence: 99%